Method for analyzing coating falling reason in aluminum-silicon coating differential thickness rolling process
By using shearing samples, bending tests, wire cutting samples, cleaning surfaces, corrosion and electronic probe observation methods in the differential thickness rolling process of aluminum-silicon coated steel, the problem of difficult to determine the cause of plating peeling is solved, and the accurate analysis and detection of the reasons for plating peeling is achieved, which reduces production costs and improves product quality.
Patent Information
- Application Number
- CN202510213836.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-06-10
AI Technical Summary
During the poor thickness rolling process of aluminum-silicon coated steel, the coating is prone to fall off, and the existing detection methods cannot systematically and in-depth analysis of the reasons for the fall off, resulting in increased production costs and decreased product quality.
A method including shearing samples, bending tests, wire cutting samples, cleaning surfaces, corrosion and observation of electronic probes is adopted. Through the coordination of corrosion agent and electronic probes, the phase structure, morphology, size and distribution of the fan-shaped radial FeSiAl4 phase that causes the plating to fall off is clearly displayed, and the components of the FeSiAl4 phase and the atomic ratio of each element are accurately determined through the electronic probes.
This method can accurately determine the cause of the plating peeling, and has the characteristics of low detection cost, fast, simple and accurate, filling the gap in the existing technology that lacks systematic and in-depth analysis methods.
Smart Images

Figure CN120121650A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metallographic analysis and detection, and particularly relates to a method for analyzing the cause of coating peeling during the differential thickness rolling of an aluminum-silicon coating. Background Art
[0002] In modern industrial production, aluminum-silicon coated steel is widely used in many fields such as automobiles and construction due to its excellent corrosion resistance, heat resistance, and processing performance. However, during the differential thickness rolling process, the problem of coating peeling has become a key factor restricting its further promotion and application. Coating peeling not only reduces the corrosion resistance of the product and affects its service life, but also may lead to an increase in the scrap rate during the production process, increasing production costs and resource waste. For steel used in hot stamping forming, coating peeling causes oxidation at the peeling position. Currently, for the cause of coating peeling during the differential thickness rolling process, the cross-sectional metallographic method and the direct analysis method combining scanning electron microscopy and energy dispersive spectrometer are used. The cross-sectional metallographic method can only show that the coating at the peeling position does not exist and cannot find the cause of peeling. The direct analysis method combining scanning electron microscopy and energy dispersive spectrometer can only show that the coating at this position peels off, and the composition can only be determined as the composition of the aluminum-silicon coating and cannot find the cause of peeling. Therefore, the research on this problem is still insufficient, lacking a systematic and in-depth method for analyzing the cause of coating peeling.
[0003] Therefore, there is an urgent need to create a new detection method that can directly determine the cause of coating peeling during the differential thickness rolling of an aluminum-silicon coating, fill the technical gap in related fields, provide strong theoretical support and practical guidance for optimizing the production process and improving product quality, and promote the wider application and sustainable development of aluminum-silicon coated steel in various industries. Summary of the Invention
[0004] To solve the above technical problems, the present invention provides a method for analyzing the cause of coating peeling during the differential thickness rolling of an aluminum-silicon coating, which can clearly show the phase structure, morphology, size, and distribution of the fan-shaped and radially distributed FeSiAl 4 phase that causes coating peeling during the differential thickness rolling of the aluminum-silicon coating. Through the electron probe, the composition of the FeSiAl 4 phase and the atomic ratio of each element can be accurately determined, and it has the characteristics of low detection cost, fast speed, simplicity, and accuracy.
[0005] To achieve this technical purpose, the present invention adopts the following scheme: A method for analyzing the cause of coating peeling during the differential thickness rolling of an aluminum-silicon coating, including cutting a sample, bending test, wire cutting to cut the sample, cleaning the surface, corrosion, and electron probe observation; the specific operations are as follows: S1. Cut a sample, take the sample with coating peeling during the differential thickness rolling process, cut the sample with a shearing machine, and wipe the surface clean with alcohol; S2. Bending test: Mount the sample from step S1 on a bending testing machine for bending. Then, stick a tape on the deformed part of the test surface, press the tape with fingers to ensure no air bubbles at the attachment area. Then, at an angle of (60 ± 5)° between the tape and the specimen, quickly tear off the tape once, visually inspect and mark the position where the coating peels off. S3. Wire-cut the specimen: Take the sample from step S2 and wire-cut the specimen at the marked position. S4. Clean the surface: Put the specimen cut in step S3 into a beaker, add alcohol and a cleaning agent, and then put the beaker into an ultrasonic cleaner for cleaning. S5. Corrosion: Immerse the cleaned specimen in a corrosive agent for 1 - 10 minutes, take it out, rinse it clean, and dry it. S6. Electron probe observation: Place the specimen prepared in step S5 under an electron probe for observation. The acceleration voltage is 20 KV, and use a spectrometer to quantitatively analyze the composition of the phase to determine the cause of coating peeling.
[0006] The preferred solution of the present invention is: A method for analyzing the cause of coating peeling during differential thickness rolling of an aluminum-silicon coating, including cutting the specimen, bending test, wire-cutting the specimen, cleaning the surface, corrosion, and electron probe observation; the specific operations are as follows: S1. Cut the specimen: Take the sample with coating peeling during differential thickness rolling, cut the sample with a shearing machine, the sample size is 75 - 125 mm × 300 mm, and wipe the surface clean with alcohol. S2. Bending test: Mount the sample from step S1 on a bending testing machine for bending. The specific operation is as follows: Take the sample from step S1, mount the sample on the bending testing machine, ensure that the supporting surface of the sample is perpendicular to the bending axis, and both ends of the sample are within the jaws of the bending machine. Bend it uniformly, bend it under the action of force until the two arms are parallel to each other, and unload the sample; then use a tape with a bonding strength of (11 ± 1) N / 25 mm to stick on the deformed part of the test surface, press the tape with fingers to ensure no air bubbles at the attachment area. Then, at an angle of (60 ± 5)° between the tape and the specimen, quickly tear off the tape once, visually inspect and mark the position where the coating peels off. Preferably, the temperature for the bending test of the sample is 10 - 35 °C, and the bending speed is 1 mm / min - 5 mm / min. S3. Wire-cut the specimen: Take the sample from step S2 and wire-cut the specimen at the marked position. The specimen size is 8 - 15 mm × 8 - 15 mm. S4. Clean the surface: Put the specimen cut in step S3 into a beaker, add alcohol and a cleaning agent, and then put the beaker into an ultrasonic cleaner for cleaning. The specific operation is as follows: Put the sample cut in step S3 into a beaker, add 30 ml to 50 ml of alcohol and 1 g to 3 g of cleaning agent, then put the beaker into an ultrasonic cleaner for cleaning. Set the output power of the ultrasonic cleaner to 30% to 50% and the temperature to 18°C to 22°C, clean for 3 to 5 minutes, take out, and rinse clean with alcohol; S5. Corrosion: Put the cleaned sample into the corrosion agent for corrosion for 1 to 10 minutes, take out, rinse clean, and dry; The corrosion agent is prepared from 50 to 80 ml of 5% to 20% sulfuric acid aqueous solution and 1 g to 3 g of stannous chloride at room temperature; The specific operation is as follows: Put the cleaned sample into the corrosion agent for corrosion for 1 to 10 minutes. The coating surface bulges due to the reaction. Then use tweezers to lift the bulged coating in the corrosion solution. After observing that the surface no longer reacts, turn the sample over in the corrosion solution until the coating surface bulges due to the reaction. Then use tweezers to lift the bulged coating in the corrosion solution. After observing that the surface no longer reacts, wear rubber gloves, take out the sample from the corrosion solution, and rub the surface with hands while taking it out. Take it out and immediately rinse it under water until the surface is clean, then rinse it clean with alcohol and dry; S6. Electron probe observation: Put the sample prepared in step S5 under the electron probe for observation. The acceleration voltage is 20 KV, and use a spectrometer to quantitatively analyze the composition of the phase to determine the reason for the coating peeling off.
[0007] The reason for the coating peeling off is the presence of abnormally grown FeSiAl 4 phases with a fan-shaped radial distribution.
[0008] Compared with the prior art, the beneficial effects of the present invention are as follows: The method of the present invention can clearly show the phase structure morphology, size, and distribution of the thick and fan-shaped radial distribution of FeSiAl 4 phases that cause the coating to crack and peel off during the differential thickness rolling of the coating through the cooperation of the corrosion agent and the electron probe. The composition of the phase and the atomic ratio of each element can be accurately determined by the electron probe, and it has the characteristics of low detection cost, fast speed, simplicity, and accuracy.
[0009] The corrosion agent used in the present invention is prepared from 50 to 80 ml of 5% to 20% sulfuric acid aqueous solution and 1 g to 3 g of stannous chloride at room temperature. This corrosion agent has low cost, is safe and non-toxic, and is convenient to configure. It can clearly and completely show the phase structure, morphology, size, and distribution of the radial FeSiAl 4 phases that cause the coating to peel off during the differential thickness rolling of the aluminum-silicon coating.
[0010] During production, it was found that the coating peeled off during the differential thickness rolling process. However, the coating peeling was local, with the peeling positions unevenly distributed and difficult to determine. The method of the present invention can accurately determine the specific positions of local coating peeling during the differential thickness rolling process through two shear and bending tests, and then directly and accurately determine the cause of coating peeling after sampling and analysis. Description of the Drawings
[0011] Figure 1 For the thick and radially distributed FeSiAl at the coating peeling position in Example 1 4 Phase structure diagram; Figure 2 For the detection result diagram of the cross-sectional metallography method used in Comparative Example 1; Figure 3 For the thick and radially distributed FeSiAl at the coating peeling position in Example 2 4 Phase structure diagram; Figure 4 For the direct detection result diagram of the scanning electron microscope used in Comparative Example 2; Figure 5 For the thick and radially distributed FeSiAl at the coating peeling position in Example 3 4 Phase structure diagram. Detailed Description of the Invention
[0012] To fully understand the purpose, features, and effects of the present invention, the present invention will be described in detail through the following specific embodiments, but the present invention is not limited thereto. Example 1
[0013] A method for analyzing the cause of coating peeling during the differential thickness rolling of an aluminum-silicon coating, including cutting a sample, bending test, wire cutting to cut the sample, cleaning the surface, corrosion, observing the morphology of the phase with an electron probe, and accurately determining the composition of the phase to determine the cause of coating peeling during the differential thickness rolling process; specifically: S1. Sampling: Take a 1.5 mm aluminized silicon plate (grade T1500HS+AS), a sample with coating peeling during 10% differential thickness rolling, cut the sample with a shearing machine to a size of 75 mm×300 mm, and clean the surface with alcohol.
[0014] S2. Bending test: Install the sample obtained in step S1 on a bending test machine, ensure that the support surface of the sample is perpendicular to the bending axis, and both ends of the sample are located within the jaws of the bending machine. Bend at a constant speed of 1 mm / min until the two arms are parallel to each other under the action of force, and unload the sample; then use a tape with an adhesive strength of 10 N / 25 mm to paste it on the deformed part of the test surface, press the tape with your finger to make there be no bubbles at the attachment, and then quickly tear off the tape at a 55° angle between the tape and the sample once, visually observe and mark the coating peeling position.
[0015] S3. Wire cutting to obtain specimens: Take the sample from S2 and use wire cutting to obtain specimens at the marked peeling-off position, with the size of 8mm×8mm.
[0016] S4. Clean the surface: Put the sample after wire cutting in step S3 into a beaker, add 30 ml of alcohol and 1 g of cleaning agent, put the beaker into an ultrasonic cleaner for cleaning, set the output power of the ultrasonic cleaner to 30%, the temperature to 22°C, clean for 5 minutes, take out, and rinse thoroughly with alcohol.
[0017] The cleaning agent can be any one of the existing cleaning agents, which is used to remove the pollutants after wire cutting. Preferably, it is a weakly acidic or neutral cleaning agent. In this application, the cleaning agent is Seagull shampoo. The ultrasonic cleaner can be any one of the existing equipment. In this application, Chunlin ultrasonic cleaner is used, and the output power of the ultrasonic cleaner is set to 30 - 50%.
[0018] S5. Corrosion: Put the cleaned specimen into the corrosion agent prepared from 50 ml of 5% sulfuric acid aqueous solution and 1 g of stannous chloride at room temperature for corrosion for 1 min until the coating surface bulges due to the reaction. Then use tweezers made of iron or stainless steel to lift the bulged coating in the corrosion solution. After observing that the surface no longer reacts, turn the sample over in the corrosion solution until the coating surface bulges due to the reaction. Then use tweezers made of iron or stainless steel to lift the bulged coating in the corrosion solution. After observing that the surface no longer reacts, wear rubber gloves, take out the sample from the corrosion solution, rub the surface by hand while taking it out, immediately rinse it under cold water until the surface is clean, then rinse it thoroughly with alcohol and dry it.
[0019] S6. Observe the morphology of the phase and accurately determine the composition of the phase by electron probe: The electron probe can be any one of the existing equipment. In this application, the model used is JXA-iHP200F EPMA. The specific operation is to put the prepared specimen under the electron probe for observation. The acceleration voltage is 20 KV, and use a spectrometer to quantitatively analyze the composition of the phase. The abnormally grown FeSiAl in a fan-shaped radial distribution that causes the coating to peel off during differential thickness rolling can be clearly observed 4 phase, and the results are shown in Figure 1 , use a spectrometer to accurately determine the composition of the phase, and determine it as FeSiAl 4 phase according to the atomic percentage. The results are shown in Table 1.
[0020] Table 1 Atomic ratios of each element of the FeSiAl 4 phase with a fan-shaped divergent distribution that causes the coating to peel off during differential thickness rolling in Example 1
[0021] Comparative Example 1: Using the cross-sectional metallographic method can only observe peeling but cannot find the reason The cross-sectional metallographic method can only observe the peeling off but cannot find the cause. The steps include wire cutting to obtain specimens, hot embedding, grinding, polishing, etching, and observing with a metallurgical microscope. The specific steps are as follows: (1) Sampling: Take a 1.5-mm aluminized silicon plate (grade T1500HS+AS), a sample with coating peeling off during 10% differential thickness rolling. Use wire cutting to obtain a specimen at the peeling-off location, with a size of 8 mm×8 mm. (2) Hot embedding: Vertically place the sample from step (1) into an embedding machine for embedding, which takes 10 minutes. (3) Grinding: The embedded specimen is coarsely ground with 280# metallographic sandpaper until the scratch directions are consistent. After rotating 90°, it is finely ground with 600# sandpaper until the previous scratches disappear. After rotating 90° again, it is finely ground with 800# sandpaper until the previous scratches disappear. This process takes 10 minutes. (4) Then perform polishing treatment. Specifically, evenly spray water and 2.5-μm high-efficiency metallographic polishing agent on a 250-mm pressure-sensitive adhesive nylon polishing cloth in sequence, and then polish at a polishing machine speed of 600 revolutions per minute for 2 minutes. (5) Etching with 4% nitric acid alcohol: The sample from step (4) is etched with 4% nitric acid alcohol for 2 - 3 seconds, rinsed clean with alcohol, and dried with a hair dryer. (6) Observe under a metallurgical microscope. Only the peeled-off coating can be observed, and the cause of coating peeling off cannot be found. See specifically Figure 2 . Example 2
[0022] A method for analyzing the cause of coating peeling off during differential thickness rolling of an aluminum-silicon coating, including cutting specimens, bending test, wire cutting to obtain specimens, cleaning the surface, etching, observing the morphology of phases with an electron probe, and accurately determining the composition of phases to determine the cause of coating peeling off during differential thickness rolling. Specifically: S1. Sampling: Take an 1.8-mm aluminized silicon plate (grade T1500HS+AS), a sample with coating peeling off during 20% differential thickness rolling. Use a shearing machine to cut a sample with a size of 100 mm×300 mm, and clean the surface with alcohol.
[0023] S2. Bending test: Install the sample from step S1 on a bending testing machine, ensure that the supporting surface of the sample is perpendicular to the bending axis, and both ends of the sample are located within the jaws of the bending machine. Bend at a constant speed of 3 mm / min until the two arms are parallel to each other under the action of force, and unload the sample. Then use a tape with a bonding strength of 11 N / 25 mm to stick on the deformed part of the test surface, press the tape with fingers to make no bubbles at the attachment, and then quickly tear off the tape at a 60° angle between the tape and the specimen, visually observe and mark at the coating peeling-off position.
[0024] S3. Wire cutting to obtain specimens: Take the sample from S2 and use wire cutting to obtain specimens at the position where the mark has fallen off. The size is 10 mm × 10 mm.
[0025] S4. Clean the surface: Put the sample after wire cutting in step S3 into a beaker, add 40 ml of alcohol and 2 g of Seagull shampoo. Set the output power of the ultrasonic cleaner to 40% and the temperature to 20 °C, clean for 4 minutes, take out, and rinse thoroughly with alcohol.
[0026] S5. Corrosion: Put the cleaned specimen into the corrosion solution prepared from 80 ml of 10% sulfuric acid aqueous solution and 2 g of stannous chloride at room temperature. The corrosion time is 5 minutes until the coating surface bulges due to the reaction. Then use tweezers made of iron or stainless steel to lift the bulged coating in the corrosion solution. After observing that the surface no longer reacts, turn the sample over in the corrosion solution until the coating surface bulges due to the reaction. Then use tweezers made of iron or stainless steel to lift the bulged coating in the corrosion solution. After observing that the surface no longer reacts, wear rubber gloves, take out the sample from the corrosion solution, rub the surface by hand while taking it out, immediately rinse it under cold water until the surface is clean, then rinse it thoroughly with alcohol and dry it.
[0027] S6. Use an electron probe to observe the morphology of the phase and accurately determine the composition of the phase. Put the prepared specimen under the electron probe for observation. The acceleration voltage is 20 KV. Use a spectrometer to quantitatively analyze the composition of the phase. The abnormally grown FeSiAl with a fan-shaped radial distribution that causes the coating to fall off during differential thickness rolling can be clearly observed. 4 phase, and the results are shown in Figure 3 . Use a spectrometer to accurately determine the composition of the phase. According to the atomic percentage, it is determined to be FeSiAl 4 phase, and the results are shown in Table 2.
[0028] Table 2 Atomic ratios of elements of the FeSiAl 4 phase with a fan-shaped divergent distribution that causes the coating to fall off during differential thickness rolling in Example 2
[0029] Comparative Example 2: Scanning electron microscopy observation + energy dispersive spectrometer directly observes the falling-off position Use scanning electron microscopy observation + energy dispersive spectrometer to directly observe the coating at the falling-off position. The specific steps are as follows: (1) Use a shearing machine to cut a sample of 8 × 10 mm. The grade is the same as that in Example 2.
[0030] (2) Put the sample into a beaker containing alcohol, clean the surface with an ultrasonic cleaner for 5 minutes, take it out, and dry it with a hair dryer.
[0031] (3) Observe under a scanning electron microscope. Use an energy spectrometer to select the position where the coating has peeled off and qualitatively analyze the composition. Since energy spectrometry is a micro-area analysis, direct scanning electron microscope + energy spectrometer analysis cannot identify different phase structures and has no characteristic morphology. The results are shown in Figure 4 , and the direct energy spectrometer test results can only show the composition of the aluminum-silicon coating. There are no characteristic elements, and the reasons for the coating peeling off during differential thickness rolling of the coating cannot be detected. The results are shown in Table 3.
[0032] Table 3 Results of detecting the composition by direct scanning electron microscope observation with an energy spectrometer Example 3
[0033] A method for analyzing the reasons for coating peeling off during differential thickness rolling of an aluminum-silicon coating, including cutting samples, bending tests, wire cutting to cut samples, cleaning the surface, corrosion, observing the morphology of phases with an electron probe, and accurately determining the composition of phases to determine the reasons for coating peeling off during differential thickness rolling; specifically: S1. Sampling: Take a 1.5 mm aluminized silicon plate (grade T1800HS+AS), a sample where the coating has peeled off during 50% differential thickness rolling, and use a shearing machine to cut the sample to a size of 125 mm×300 mm. Wipe the surface clean with alcohol.
[0034] S2. Bending test: Install the sample from step S1 on a bending testing machine, ensure that the support surface of the sample is perpendicular to the bending axis, and both ends of the sample are located within the jaws of the bending machine. Bend at a constant speed of 5 mm / min until the two arms are parallel to each other under the action of force, and unload the sample; then use a tape with an adhesive strength of 12 N / 25 mm to stick it on the deformed part of the test surface, press the tape with your finger to make no bubbles at the attachment, and then quickly tear off the tape at a 62° angle between the tape and the sample, visually observe and mark the position where the coating has peeled off.
[0035] S3. Wire cutting to cut samples: Take the sample from S2 and use wire cutting to cut a sample at the peeling mark, with a size of 9 mm×9 mm.
[0036] S4. Cleaning the surface: Put the sample after wire cutting in step S3 into a beaker, add 50 ml of alcohol and 3 grams of Sea-Gull shampoo. Set the output power of the ultrasonic cleaner to 50% and the temperature to 18 °C, clean for 3 minutes, take out, and rinse clean with alcohol.
[0037] S5. Corrosion: Place the cleaned specimen into the corrosion solution prepared from 80 ml of 20% sulfuric acid aqueous solution and 3 g of stannous chloride at room temperature. The corrosion time is 10 minutes until the coating surface bulges due to the reaction. Then, use iron or stainless-steel forceps to lift the bulged coating in the corrosion solution. After observing that the surface no longer reacts, turn the sample over in the corrosion solution until the coating surface bulges due to the reaction again. Then, use iron or stainless-steel forceps to lift the bulged coating in the corrosion solution. After observing that the surface no longer reacts, wear rubber gloves, take out the sample from the corrosion solution, rub the surface by hand while taking it out, immediately rinse it under cold water, and then rinse it clean with alcohol and dry it.
[0038] S6. Observation of the morphology of the phase and precise determination of the composition of the phase by electron probe: Place the prepared specimen under the electron probe for observation. The accelerating voltage is 20 KV. Use a spectrometer to quantitatively analyze the composition of the phase. The abnormally grown FeSiAl with a fan-shaped radial distribution that causes the coating to peel off during differential thickness rolling can be clearly observed. 4 phase, and the results are shown in Figure 5 . Use a spectrometer to precisely determine the composition of the phase, and it is determined to be FeSiAl according to the atomic percentage. 4 phase, and the results are shown in Table 4.
[0039] Table 4 Atomic ratios of each element of the FeSiAl with a fan-shaped divergent distribution that causes the coating to peel off during differential thickness rolling in Example 3 4 Atomic ratios of each element of the
[0040] There is an abnormally grown FeSiAl with a fan-shaped radial distribution in the alloy layer. 4 This abnormally grown FeSiAl with a fan-shaped radial distribution 4 phase causes extremely poor deformability of the alloy layer during differential thickness rolling, resulting in the coating peeling off between the alloy layer and the aluminum-silicon layer. During production, it is found that the coating peels off during differential thickness rolling, but the coating peeling is local, the peeling positions are unevenly distributed and difficult to determine, and the FeSiAl 4 phase is unevenly distributed and is covered with a coating on the outside. Therefore, it is very difficult to determine the cause of the coating peeling. However, the method of the present invention can precisely determine the specific position of the local coating peeling during differential thickness rolling through two shear and bending tests, and then directly and accurately determine the cause of the coating peeling after sampling and analysis. It can clearly show the abnormally grown FeSiAl with a fan-shaped radial distribution that causes the coating peeling. 4 phase, and can precisely determine the phase structure, morphology, size and distribution of the FeSiAl 4 phase, providing a basis for subsequent improvement research.
[0041] Finally, it should be noted that the above-listed are only the preferred embodiments of the present invention. Of course, those skilled in the art can make changes and modifications to the present invention. Provided that these modifications and variations fall within the scope of the claims of the present invention and its equivalent technologies, they should all be considered within the protection scope of the present invention.
Claims
1. A method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating, characterized in that: It includes cutting samples, bending test, wire cutting samples, surface cleaning, corrosion and electron probe observation; the specific operations are as follows: S1. Cut the sample, take the sample with the coating peeled off during the differential thickness rolling process, cut the sample with a shearing machine, and clean the surface with alcohol; S2, bending test, install the sample in step S1 on a bending tester and bend it, then stick the tape on the deformed part of the test surface, press the tape with your fingers to make sure there are no bubbles at the attachment, then tear off the tape quickly at one time at an angle of (60±5)° between the tape and the sample, visually inspect and mark the location where the coating falls off; S3, cutting the sample by wire cutting, taking the sample in step S2 and cutting the sample by wire cutting at the marked position; S4, cleaning the surface, placing the sample cut in step S3 into a beaker, adding alcohol and a cleaning agent, and then placing the beaker into an ultrasonic cleaner for cleaning; S5. Corrosion: put the cleaned sample into the corrosive agent for 1 to 10 minutes, take it out, rinse it, and blow it dry; S6. Electron probe observation: the sample prepared in step S5 is placed under an electron probe for observation at an accelerating voltage of 20 KV. A spectrometer is used to quantitatively analyze the phase composition to determine the cause of coating shedding.
2. The method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating according to claim 1, characterized in that: The sample size in step S1 is 75~125mm×300mm.
3. The method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating according to claim 1, characterized in that: The specific operation of the bending test in step S2 is as follows: take the sample of step S1, install the sample on the bending tester, ensure that the supporting surface of the sample is perpendicular to the bending axis, and the two ends of the sample are located in the jaws of the bending machine, bend at a uniform speed, bend until the two arms are parallel to each other under the action of force, and unload the sample; then use a tape with a bonding strength of (11±1) N / 25mm to stick it on the deformed part of the test surface, press the tape with your fingers to make sure there are no bubbles at the attachment, and then quickly tear off the tape at an angle of (60±5)° between the tape and the sample, visually inspect and mark the location where the coating falls off.
4. According to the method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating as described in claim 3, the bending test temperature is 10~35°C, and the bending speed is 1mm / min~5mm / min.
5. The method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating according to claim 1, characterized in that: The sample size in step S3 is 8~15mm×8~15mm.
6. The method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating according to claim 1, characterized in that: The specific operation of step S4 is: put the sample cut in step S3 into a beaker, add 30ml~50ml alcohol and 1~3g cleaning agent, and then put the beaker into an ultrasonic cleaner for cleaning. The output power of the ultrasonic cleaner is set to 30~50%, the temperature is set to 18~22℃, and the cleaning is carried out for 3-5min. Take it out and rinse it with alcohol.
7. The method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating according to claim 1, characterized in that: The etchant in step S5 is prepared from 50-80 ml of 5-20% sulfuric acid aqueous solution and 1-3 g of stannous chloride at room temperature.
8. The method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating according to claim 1, characterized in that: The specific operation of step S5 is: put the cleaned sample into the corrosive agent for corrosion for 1 to 10 minutes, the surface of the coating bulges due to the reaction, then use tweezers to lift up the bulged coating in the corrosive solution, observe the surface reaction and then turn the sample over in the corrosive solution until the surface of the coating bulges due to the reaction, then use tweezers to lift up the bulged coating in the corrosive solution, observe the surface reaction and then put on rubber gloves, take the sample out of the corrosive solution, rub the surface with hands while taking it out, rinse it underwater immediately after taking it out, rinse it with alcohol after the surface is clean, and blow it dry.
9. The method for analyzing the cause of coating shedding during differential thickness rolling of aluminum-silicon coating according to claim 1, characterized in that: The reason why the coating falls off in step S6 is the presence of abnormally grown FeSiAl4 phase distributed radially in a fan shape.
Citation Information
Patent Citations
Zinc-aluminum-magnesium coating and zinc-aluminum-magnesium coating steel plate
CN115558877A
Method for determining reason of needle-shaped skip plating on surface of aluminized silicon plate
CN116818820A
Method for analyzing scale falling reason after 22MnB5 hot stamping forming
CN117705809A
Method for analyzing plating leakage reason of aluminum-silicon plating layer taking stainless steel as substrate
CN117723363A
Method for measuring thickness of alloy coating
CN118463871A